Is routine drainage necessary after thyroid surgery? A randomized controlled trial study - Wang, Ziming; Qi, Peng; Zhang, Lixi; Zhang, Ben; Liu, Xuyao; Shi, Qi; Zhang, Qiang (Frontiers in Endocrinology, 2023)
Objective: To evaluate whether no drainage has an advantage over routine drainage in patients with thyroid carcinoma after unilateral thyroid lobectomy and central neck dissection. Methods: A total of 104 patients with thyroid cancer who underwent unilateral thyroid lobectomy and central lymph node dissection were randomly assigned into no drainage tube (n=52) and routine drainage tube (n=52) placement groups. General information of each patient was recorded, including the postoperative drainage volume/residual cavity fluid volume, postoperative complications, incision area comfort, and other data, and the thyroid cancer-specific quality of life questionnaire (THYCA-QoL) and patient and observer scar assessment scale (POSAS) were evaluated after surgery. At the 3–6 months follow-up exam, the differences between the two groups were compared based on univariate analysis. Results: Significant differences were not observed in the general and pathological information (including sex, age, body weight, body mass index (BMI), incision length, specimen volume, Hashimoto's thyroiditis, and number of lymph nodes dissected), operation time, and postoperative complications (postoperative bleeding, incision infection, lymphatic leakage, and temporary hypoparathyroidism) between the two groups. The patients in the non-drainage group had a shorter hospital stay (2.11±0.33 d) than the patients in the drainage group (3.38±0.90 d) (P<0.001). The amount of cervical effusion in patients in the non-drainage group (postoperative 24h: 2.20±1.24 ml/48 h: 1.53 ±1.07 ml) was significantly less than that in the drainage group (postoperative 24 hours: 22.58±5.81 ml/48 h: 36.15±7.61 ml) (all P<0.001). The proportion of incision exudation and incision numbness in the non-drainage group was lower than that in the drainage group (all P<0.05), and the pain score (VAS) and neck foreign body sensation score (FBST) decreased significantly (P<0.05). During the 3- and 6-month follow-up exams, significant differences were not observed between the THYCA-QoL and drainage groups and the non-drainage group, although the scarring and POSAS values were lower than those in the drainage group. In addition, the length of stay and cost of hospitalization in the non-drainage group were lower than those in the drainage group (P<0.05). Conclusions: Routine drainage tube insertion is not needed in patients with unilateral thyroid lobectomy and central neck dissection.